The characteristics of basic education school administrator in accordance with education goal of Thailand 4.0 - Luanpasitsakul, Tippawan; Intarak, Prasert (Saengtham College Journal, 2021)
The purpose was to identify the characteristics of basic education school administrators in accordance with the education goal of Thailand 4.0. This research design was Ethnographic Delphi Future Research: EDFR. The research methodology was comprised of 3 steps: firstly, to study the variables and determine the conceptual framework for research, and secondly to analyze the characteristics of basic education school administrators in accordance with the education goal of Thailand 4.0 and third collect information, discuss round 2 EDFR questionnaires from experts the characteristics of basic education school administrator in accordance with education goal of Thailand 4.0. The instruments for collecting the data were a semi-structured interview form and opinionnaire. In addition, there were 19 key informants who were policy proponents/minister/director-General, academicians/lecturer, civil society, and basic education school administrators. The statistics used for data analysis were median, mode, interquartile range, and content analysis. The findings of this research were as follows: The educational administrations the characteristics of basic education school administrator in accordance with education goal of Thailand 4.0 to experts’s opinions were the characteristics of basic education school administrator which composed of eleven correlation components to 91 characteristics were as follows; 1. The characteristics that are related to the goals of equality and equality of learners in the amount of 8 features 2. The characteristics that are related to the goals of the opportunities to study in the amount of 8 features 3. The characteristics that are related to the goals of the quality of the education system in the amount of 9 features 4. The characteristics that are related to the goals of the efficiency of management in the amount of 8 features 5. The characteristics that are related to the goals of effective management in the amount of 9 features 6. The characteristics that are related to the goals of the creative learning relate with Thailand 4.0 in the amount of 8 features 7. The characteristics that are related to the goals of lifelong learning and career Skills in the amount of 9 features 8. The characteristics that are related to the goals of the education create essential knowledge and skills necessary for the 21st century 9. The characteristics that are related to the goals of the responsive education of teacher changes in the amount of 8 features 10. The characteristics that are related to the goals of the responsive education of school in the amount of 8 features 11. The characteristics that are related to the goals of the laws that support education management are independent and responsible in the amount of 8 features